2010
DOI: 10.1080/02763869.2010.518915
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Twitter in a Health Sciences Library

Abstract: The NYU Health Sciences Libraries created an account on Twitter, a microblogging service, as a new outreach tool marketed to students, faculty, and staff. The team used Twitter to promote resources, events, and news. Twitter is a part of a pipeline of information that also includes the library's Web site and Facebook. Although it is difficult to measure the effectiveness of a social networking tool, the overhead of using Twitter is so low that it merits consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 1 publication
1
29
0
1
Order By: Relevance
“…Other groups to note were University departments/organizations (9%) and faculty/staff (5%). Cuddy et al (2010) found a similarly diverse set of followers in the early days of the NYU Health Sciences Libraries' Twitter account.…”
Section: Analysis Of Followersmentioning
confidence: 97%
See 2 more Smart Citations
“…Other groups to note were University departments/organizations (9%) and faculty/staff (5%). Cuddy et al (2010) found a similarly diverse set of followers in the early days of the NYU Health Sciences Libraries' Twitter account.…”
Section: Analysis Of Followersmentioning
confidence: 97%
“…While Twitter is an effective tool for broadcasting library information, the scholarly community appears to be united in the belief that Twitter should be used by academic libraries to interact with followers in order to take full advantage of the platform (Cole, 2009;Cuddy, Graham, & Morton-Owens, 2010;Del Bosque et al, 2012;Dickson & Holley, 2010;Gunton & Davis, 2012;Milstein, 2009;Sewell, 2013). Gunton and Davis (2012) suggest that limiting a library's social media activities to the distribution of information represents a failure to appreciate the interactive nature of the modern internet.…”
Section: Twitter Use By Librariesmentioning
confidence: 97%
See 1 more Smart Citation
“…3 Li and Li similarly observe that there "seems to be some confusion regarding what exactly social media is." 4 Social media has been experimented with and identified variously as a tool for enhancing the image of libraries, 5 as a digital listening post, 6 or as an intelligence gathering tool. 7 With such a variety of perspectives and approaches, the discussion around social media in libraries has been somewhat disjointed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is very little empirical evidence, which supports academic libraries' expenditure of time and labor in support of social media platforms, nor is there a clear linkage between library social media activities and patron engagement. While information science researchers have begun to study various iterations of Twitter use at academic libraries, most of this literature consists of latent content analysis on library-generated social media data (Aharony, 2010;Cuddy, Graham, & Morton-Owens, 2010;Del Bosque, Leif, & Skarl, 2012).…”
Section: Introductionmentioning
confidence: 99%